Phosphonoacetic Acid Inhibition of Frog Virus 3 Replication - Elliott, R. M. (1980)
Phosphonoacetic acid at concentrations above 200 μg/ml inhibited the replication of frog virus 3 in BHK cells. The inhibition of viral DNA replication observed in these cells was reversible and correlated with the inhibition of the virus-induced DNA polymerase activity in an in vitro assay. The synthesis of frog virus 3-induced late or γ polypeptides was also inhibited by phosphonoacetic acid, although the early (α and β) polypeptides were unaffected.